Urban public spaces, events, and gun violence: block parties, funerals, Mother's Day, and other community events - Delgado, Melvin (Springer, 2024)
Part I. Conceptual Foundation -- 1. Overview -- 2. Urban Public Spaces Part 1: Definition & Intersectionality/Social Justice -- 3. Urban Public Spaces Part 2: Multiple Dimensions -- 4. Criminological Schools of Thoughts + Capacity Enhancement -- 5. Guns, Trauma & Public Space Events -- Part 2. Celebratory and Solemn Events -- 6. Mother’s Day -- 7. Block Parties and Festivities -- 8. Houses of Worship, Funerals, Vigils, and Wakes -- 9. Other Public Space Events -- Part 3. Implications for Research, Education, & Practice -- 10. Research, Education & Practice.